OXIDATIVE STRESS MARKER IN THE AGGRESSIVE PERIODONTAL DISEASE - SALIVARY 8-HIDROXYDEOXYGUANOSINE - Mircea Grigorian; Aureliana Caraiane; Cristina Nucă; Radu Marius; Adina Petcu; Doina Paula Balaban; Victoria Badea (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study In this study we aimed to identify if there is a correlation between the oxidative stress marker 8-hidroxydeoxyguanosine (8-OHdG) from saliva and the orodental clinical status, evaluated by periodontal pocket depth, in aggressive periodontitis. Material and methods The study group was formed by 54 subjects (healthy control, patients with aggressive periodontitis (AgP) and periodontal pocket depth (PPD) between 4 to 5 mm and patients with AgP and PPD between 6-9 mm), which were clinical oro-dental evaluated. We measured the salivary 8-OHdG biomarker by using ELISA method, competitive technique. Results We identified statistically significant differences between the amount of salivary 8-OHdG quantified in healthy group versus AgP patients with PPD 4-5 (p=0.039) and also versus patients with PPD 6-9 (p=0.0001). In our study we also identified a high statistical correlation between the level of salivary 8-OHdG and the PPD of AgP patients (r=0.0446, p=0.005). Conclusions The results of our study demonstrate that salivary 8-OHdG oxidative stress biomarker can be used in the diagnosis and monitoring of aggressive periodontal disease.